Analisis Bahan Ajar Kimia SMA/MA Analisis Bahan Ajar Kimia SMA/MA Berdasarkan Pendekatan Science, Technology, Engineering and Mathematic (STEM): Analisis Bahan Ajar Kimia SMA/MA Berdasarkan Pendekatan Science, Technology, Engineering and Mathematic (STEM) - Eva Pratiwi Pane; Anita Debora Br Simangunsong; Ropinus Sidabutar; Gayus Simarmata (PendIPA Journal of Science Education, 2024)
Good teaching materials have certain criteria or certain standards, such as their relevance to the current curriculum. The STEM approach offers teachers the opportunity to introduce students to various concepts to teach teaching materials that can be integrated into natural sciences including chemistry. This research aims to describe the presentation of STEM aspects in class XI high school chemistry teaching materials regarding reaction rates. The method in this research is a qualitative descriptive method with a content analysis approach. The data source comes from three books for class XI high school chemistry teaching materials which are most widely used in Pematangsiatar City. The technique for selecting research objects uses purposive sampling technique. Data collection was carried out analyzing material based on STEM indicators. Testing the validity of the instrument uses the Gregory formula, while testing the validity of the data uses data triangulation. The results of the research show that the percentage of quotations appearing in each book, namely in book A, has aspects of Science 30%, Technology 40%, and Mathematics 30%. In book B, the Science aspect is 19.05%, Technology 42.86%, Engineering 9.52% and Mathematics 28.57%. In book C, the Science aspect is 25%, Technology 25%, Engineering 18.75% and Mathematics 31.25%. Based on the total occurrence of STEM aspect indicators, the order of teaching materials that fulfill the STEM aspect is Book B > Book C > Book A, so that Book B has the highest number of occurrences of STEM aspect quotes.